Nonutilization of Kidneys From Donors After Circulatory Determinant of Death. Issue 6 (13th May 2022) - Lin, Yingxin; Teixeira-Pinto, Armando; Opdam, Helen; Chapman, Jeremy R.; Craig, Jonathan C.; Rogers, Natasha; Pleass, Henry; Davies, Christopher; McDonald, Stephen; Yang, Jean; Lim, Wai; Wong, Germaine
Abstract : Background: The expansion of donation after circulatory determination of death (DCDD) programs and unmet demands for kidney transplantation indicate that there is a need to improve the efficiency and utilization of these organs. Methods: We studied all DCDD donors retrieved for kidney transplantation in Australia between 2014 and 2019 and determined the factors associated with nonutilization using least absolute shrinkage and selection operator and random forest models. Self-organizing maps were used to group these donors into clusters with similar characteristics and features associated with nonutilization were defined. Results: Of the 762 DCDD donors, 116 (15%) were not utilized for kidney transplantation. Of the 9 clusters derived from self-organizing map, 2 had the highest proportions of nonutilized kidneys. Factors for nonutilization (adjusted odds ratio [95% confidence interval], per SD increase) were duration from withdrawal of cardiorespiratory support till death (1.38 [1.16-1.64]), admission and terminal serum creatinine (1.43 [1.13-1.85]) and (1.41 [1.16-1.73]). Donor kidney function and duration of warm ischemia were the main factors for clinical decisions taken not to use kidneys from DCDD donors. Conclusions: Donor terminal kidney function and the duration of warm ischemia are the key factors for nonutilization of DCDD kidneys. Strategies to reduce the duration of warm ischemia and improve post-transplant recipient kidney function may reduce rates of nonutilization.